Semantic-syntactic Dependency Varieties of the Subject of Action in Joseph Strutsiuk’s Prose (Linguostylistic Studies, 2019)
The article highlights the varieties of semantic-syntactic dependency of the subject of action in Joseph Strutsuk’s prose. The study deals with the components of the sentence and analyzes their functional features in terms of the syntactic dependencies concept. The semantic-syntactic aspect of a sentence structure allows tracing the peculiar features of a sentence component semantic expression and revealing the correlation between the form and content in it. The concepts of ‘dependency’ and ‘valency’ are distinguished. The valency is analyzed at the morphological level in accordance with different parts of speech. In terms of the semantic-syntactic structure of the sentence, the dependency is clearly focused on the study of sentence components, controled by the predicate. The number of components in the semantic-syntactic structure of a sentence depends on its semantic features. When studying the semantic-syntactic structure of a sentence, in the focus of attention is the concept of subject dependency. In the semantic-syntactic structure of the sentence predicates determine the subject dependence of three main varieties: 1) dependence of the action subject; 2) dependence of the process subject: 3) dependence of the state subject. The study has defined main lexical groups of predicates of action. The semantics of the subject of the action depends on the semantics of the predicate. In Joseph Strutsiuk’s prose the dependency of subject is represented by 24 semantic groups. The semantic potential of the predicates of action determines the number of subject components and influences their significant differentiation. The dependency analysis reflects the main tendencies of the semantic-syntactic structure of the sentence. The dependency syntax is challenging and promising topic for further researches.
Keywords: structure of sentence; semantic-syntactic dependency; predicate of action; subject of action